IMPLEMENTASI BATUK EFEKTIF DAN FISIOTERAPI DADA PADA TN. M DENGAN TUBERCULOSIS PARU - Defina Puspitasari; Suci Khasanah (Poltekkes Kemenkes Kalimantan Timur, 2022)
Tuberculosis (TB) is an infectious disease that usually attacks the lungs and is caused by the bacterium Mycobacterium tuberculosis, although it can affect any organ in the body. Tuberculosis infection develops when bacteria enter through droplets in the air. The purpose of this scientific paper is to describe nursing care in pulmonary tuberculosis patients with ineffective airway clearance problems. The method used is a descriptive case study with the subject of one pulmonary tuberculosis patient with ineffective airway clearance problems. The pharmacological therapy given was Memucil Tab 2x1 oral administration to thin the phlegm, non-pharmacological measures were effective coughing and chest physiotherapy was carried out for three days every morning. The results of giving an effective cough and chest physiotherapy can remove the retained phlegm and then dispose of the phlegm in a special or closed place not carelessly. Conclusion: effective cough and chest physiotherapy are effective against ineffective airway clearance in pulmonary tuberculosis patients. Therefore, it is expected that nurses can provide effective coughing and chest physiotherapy therapy as a complement to pharmacological therapy to help overcome ineffective airway clearance in pulmonary tuberculosis patients.